Values of our times : contemporary axiological research in China - Li, Deshun (Springer Berlin Heidelberg, 2013)
Philosophers have gradually accepted axiology as one branch of philosophy. As a basic category belonging to axiology and philosophy, "value" is the general abstraction of concrete value formation in various fields including utility, ethics and appreciation of the beauty. The problem of value is essentially a problem of historical activities of practice in human society. The axiology based on the scientific practice view insists on the principle of unification between theory and practice, truth and value. In research of axiology, the relation between subjectivity and objectivity of values is a problem that must be solved in the first place. The modern conversation of value philosophy is the academic and practical demands of the value philosophy research in China. Value evaluation is an important part of the axiology. In order to deepen the research of value philosophy and to promote the development of current value philosophy, we must have scientific mode of thinking suitable for the nature of value. It is the base of value relation, the origin of value needs, the process of value creation and actualization and the fundamental way to proving ones value as a human being.